Effects of nitrite and pH on a tropical fish fry, puntius gonionotus (Bleeker) - Md Yusoff, Fatimah; Law, A. T.; Goh, Y. J.; Subasinghe, Rohana (Universiti Putra Malaysia Press, 1998)
The effects of short term and long term exposure of a tropical fish fry, Barbodes gonionotus (Bleeher), to pH and nitrite separately and in combination, were evaluated using static and flow-through bioassays respectively. The 96-hour LC50 values of pH and nitrate were 4.9 and 7.91 mg/l N02-N -respectively. However the 96-hour LC50 of pH was higher (5.4 pH unit) in the presence of nitrite 5.00 mg/l N02-N) than that without nitrite. At pH 5.00,100% mortality was found at 4.00 mg/l N02-N concentration after 48-hour exposure. Under long-term exposure, the growth rates of the fish fry decreased with increased nitrite concentrations. Fish fry grown at 2.00 mg/l N02-N had significantly lower growth rate (P < 0.05) than the control, but had a significantly higher rate (P < 0.05) than in the 4.00 mg/l N02-N (PH 7.33-7.56). One hundred per cent mortality occurred within 30 days at pH 5.00 - 7.00 when the fish were exposed to 4.00 mg/l N02-N concentration at the same time. The study demonstrated that the effects of combined pH and nitrite on the survival and growth rates of the fish fry were more serious than the effects of each factor separately.